The Effect of Silver Water (Ag) Administration on NF-κB Expression and Histopathology of Gastric in Rats Model of Inflammatory Bowel Disease - Putri, Cindy Ercha Aulia; Rahmatullah, Aldin Akbar; Roosdiana, Anna; Oktanella, Yudit (Archives of Veterinary Science, 2025)
Abstract: This study investigated the therapeutic effects of silver water on indomethacin-induced Inflammatory Bowel Disease (IBD) in rats. Male white rats (12 weeks old, ~250g) were divided into five groups: negative control (untreated), positive control (indomethacin-induced), and three treatment groups (T1, T2, T3) receiving 1, 2, and 3 ml of 25 ppm silver water, respectively for 14 days following indomethacin induction (15 mg/kg BW). The study evaluated NF-κB expression via immunohistochemistry and gastric histopathological changes using hematoxylin-eosin staining. Data were analyzed using ANOVA followed by the Tukey test (α = 0.05). Results demonstrated that silver water therapy at all tested volumes significantly reduced NF-κB expression, inflammatory cell infiltration, and epithelial erosion in gastric tissues compared to the positive control. The 3 ml dose showed the most pronounced therapeutic effect. These findings suggest that silver water possesses anti-inflammatory properties that suppress the NF-κB inflammatory pathway and promote gastric tissue repair in indomethacin-induced IBD, potentially offering a novel therapeutic approach for IBD management.